Use of social media for cancer prevention and early diagnosis: scoping review protocol - Kaushal, Aradhna; Kassianos, Angelos P.; Sheringham, Jessica; Waller, Jo; von Wagner, Christian (My University, 2020)
Social media platforms offer unique opportunities for health promotion messages focusing on cancer prevention and early diagnosis. However, there has been very little synthesis of the evaluation of such campaigns, limiting the ability to apply learning to the design of future social media campaigns. We aimed to provide a broad overview of the current research base on social media interventions for cancer prevention and early diagnosis, to identify knowledge gaps and to inform policy, practice and future research questions.
Keywords: Social medicine; Health policy; Public health